A Thermodynamic Measure of Sustainability - Sciubba, Enrico (Frontiers in Sustainability, 2021)
A novel thermodynamic approach to the quantification of the “degree of sustainability” is proposed and discussed. The method includes a rigorous -and innovative- conversion procedure of the so-called externalities that leads to their expression in terms of the exergy of their equivalent primary resources consumption. Such a thermodynamic approach suggests a detailed re-evaluation of the concept of sustainability because it is well-known that the Second Law strictly negates the possibility for any open and evolving system to maintain itself in a “sustainable” state without availing itself of a continuous supply of low-entropy (i.e., high specific exergy) input. If a human society is modeled as an open system, its capacity to “grow sustainably” depends not only on how it uses non-renewable resources, but also on the rate at which it exploits the renewable ones. The necessary inclusion of different forms of energy- and material flows in such an analysis constitutes per se an argument in favor of a resource-based exergy metrics. While it is true that the thermodynamically oriented approach proposed here neglects all of the non-thermodynamic attributes of a “sustainable system” (in the Bruntland sense), it is also clear that it constitutes a rigorous basis on which different physically possible scenarios can be rigorously evaluated. Non-thermodynamic indicators can be still used at a “second level analysis” and maintain their usefulness to indicate which one of the “thermodynamically least unsustainable” scenarios is most convenient from an ethical or socio-economic perspective for the considered community or for the society as a whole. The proposed indicator is known as “Exergy Footprint,” and the advantages of its systematic application to the identification of “sustainable growth paths” is discussed in the Conclusions.